Using Youtube Music Video to Improve transactional Speaking Skills at The Second Grade Students Of SMA Negeri 3 Sinjai - Khatimah, Khusnul; Ahmad, Djuwairiah; Azisah, St (English Language Teaching for EFL Learners Journal, 2023)
The purpose of this research is to know the effectiveness of YouTube Music Video in teaching transactional speaking skills at the second grade of SMA Negri 3 Sinjai Timur. The pre-experimental research with pre-test and post-test was implemented as the design of the research. The population of this research was the second-grade students of SMA Negeri 3 Sinjai Timur who enrolled in the academic year 2020/2021 consist of 30 students. The technique sampling used in this research was random sampling. The sample of this research is class XI MIA 2 consists of 15 students, the instrument used to collect data was the speaking test. The data were analysed by descriptive and inferential technique statistic. The result of the research presented that the pre-test of the class got a mean score of 31.26. After giving treatment the students got a mean score of 62.86. The outcome of the data analysis revealed that there was a significant improvement in students’ transactional speaking skills using YouTube Music Video. Subsequently, it was also supported by the result of one sample t-test where Sig. (2-tailed) = 0.000 < 0.05. This implies that the treatment had a significant main effect on the students’ transactional speaking skills achievement. Therefore the null (Ho) is rejected and the alternative hypothesis (H1) is accepted. Based on the result analysis, the researcher may conclude that using YouTube Music Video was effective to improve the students Transactional Speaking skills especially at Class XI MIA 2 at SMA Negeri 3 Sinjai Timur.